Mienie i nadzór samorządu stanowego wsi piastowskiej - Waniewska, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
As a result of expansion of the feudal system, as well as due to an intensified process of colonization and economical and legal transformations, at the turn of the 12th and 13th centuries there were formed estate representative institutions. The local estate countryside administration was established as a direct consequence of the fact that some of the rights of the landowners were transferred onto communal units. The functioning of the local countryside administration was limited by law and monitored by the state authorities. Its salaries resulted partly from the concession on the part of a land proprietor, partly from the contemporaneous customary case law. The local countryside administration did not own any property as such; it could only be lent under the law of common use. The control of the local countryside authorities was based on a legally sanctioned constraint. The criterion for the supervision of this institution was its compliance with the legal norms, particularly with a location document of a given country commune.